Pengembangan Aplikasi Career Development Center - Antonius Agung Hartono; Ipo Novianto; Berlilana (Journal of Innovation Information Technology and Application (JINITA), 2021)
Alumnuses have a role in the college progress. one of the roles of alumnuses is that alumnuses provide input to college for mapping job market. Alumnuses inputs are obtained by college through tracer study at college career center. The Career Development Center (CDC) of the Cilacap State Polytechnic (PNC) conducts a tracer study process by sending a form link via short message to the group of alumnuses. The problem with this method is that the tracer study form can be filled out by everyone who has the link. On the other hand, the officer must re-enter the same list of questions for alumnuses in different years. This study aims to create a Career Development Center application that can help PNCs to monitor the distribution of alumnuses and help CDC disseminate job vacancy information. The method used in software development uses the waterfall method. At the software testing stage, the method used is blackbox testing. Based on the results of customer feedback, 30 respondents produced a very good predicate. The conclusion of this study, the development of the Career Development Center application can help spread alumni and help CDC disseminate job vacancies information to alumni.